Oral Glucoraphanin and Curcumin Supplements Modulate Key Cytoprotective Enzymes in the Skin of Healthy Human Subjects: A Randomized Trial - Anna L. Chien; Hua Liu; Saleh Rachidi; Jessica L. Feig; Ruizhi Wang; Kristina L. Wade; Katherine K. Stephenson; Aysegul Sevim Kecici; Jed W. Fahey; Sewon Kang (Metabolites)
Background/Objectives: Oxidative stress plays a pivotal role in skin aging and carcinogenesis. Phytochemicals such as sulforaphane (SF, from broccoli sprouts or seeds) or curcumin (CUR, from turmeric) can be highly protective against this stress. They each induce a suite of cytoprotective and antioxidant enzymes that are coordinately transcribed via the Keap1-Nrf2-ARE pathway in mammals, such as the prototypical cytoprotective enzyme NAD(P)H dehydrogenase 1 (NQO1). Methods: Eighteen healthy human volunteers (9 males, 9 females, aged 18–69. were randomized to receive daily glucoraphanin (GR), which is converted to SF upon ingestion (450 mg; 1 mmol), CUR (1000 mg; 2.7 mmol), or both (450 mg GR + 1000 mg CUR), as oral supplements. After 8 days of a diet low in both compounds, blood and urine were collected for compliance and biomarker measurements. Randomized spots on the buttock’s skin were exposed to 2 x M.E.D. of UVB, and punch biopsies were obtained 1 and 3 days later for biomarker and histological measurement. Erythema was measured with a chromameter daily for 3 consecutive days following UVB. The process was repeated after receiving oral supplements, both with and without UVB exposure. Results: Compared to baseline, each treatment (n = 6 for each) induced NQO1 mRNA levels in skin biopsies: 3.1-fold with GR, 3.3-fold with CUR, and 3.6-fold with the combination of GR and CUR. Across all treatments (n = 18), expression of the pro-inflammatory cytokines IL-1β and TNF-α were reduced, as were IL-6, IL-17, STING, and CYR61, though less robustly. Modulation of these biomarkers persisted, but was less pronounced, in biopsies taken following UV exposure. The presence of SF and its metabolites in the skin post-treatment was confirmed by examining 6 of 12 subjects who ingested GR. Supplement effects on erythema following UV exposure were not significant, and no significant changes were measured in the same biomarkers in blood cells (PBMC), or by counting dyskeratotic keratinocytes. Supplements were well tolerated and compliance was excellent. Conclusions: Oral GR and CUR are well tolerated and have for the first time been shown to result in increased expression of cytoprotective genes and reduced expression of inflammatory cytokine genes in human skin in vivo. This mechanism-based clinical study suggests that an antioxidant, anti-inflammatory, and cytoprotective benefit from these oral supplements is delivered to the skin in humans.